The Effect of Addition of Squid Ink (Loligo sp.) to Pizza Dough on Its Organoleptic Properties and Antioxidant Activity - Sabrina Miftahul Sidika; Eka Andriani; Al Mukhlas Fikri (Bulletin of Culinary Art and Hospitality, 2022)
The use of squid ink (Loligo sp.) in food can be an innovative opportunity for the culinary community in the manufacture of processed food products and their antioxidant content. This study aims to identify and analyze the organoleptic properties and antioxidant content of squid ink pizza dough (Loligo sp.). Organoleptic testing was carried out on pizza dough with 10, 20, and 30% addition of squid ink involving 30 semi-trained students as the panelists. Further, the samples with the best organoleptic test result were used as squid ink pizza dough samples tested for antioxidant activity analysis using the DPPH method. The antioxidant test involved three treatments, namely pizza dough with squid ink (Loligo sp.) without the baking process, pizza dough without squid ink (Loligo sp.) with the baking process, and pizza dough with squid ink (Loligo sp.) and baking process. The results showed no significant effect on organoleptic properties in hedonic testing, but there was a significant effect from the addition of 10, 20, and 30 percent squid ink (Loligo sp.) on color and taste in hedonic quality testing. Meanwhile, the antioxidant activity on pizza dough with the addition of squid ink (Loligo sp.) has an inactive antioxidant activity value (IC50 more than 200 ppm). The results of this study can be used as a reference for a food product that incorporates squid ink (Loligo sp.).